METODE JUST IN TIME (JIT) DALAM PENGELOLAAN PERSEDIAAN PADA PELAKSANAAN PROYEK KONSTRUKSI - Cut Zukhrina Oktaviani; Febriyanti Maulina (Universitas Bengkulu, 2019)
Just In Time (JIT) Methode in Construction Project Logistic Management. The aim of this research is to know the understanding description of Just In Time (JIT) concept and readiness of contractor to application JIT principal in project construction activity. Design of research is exploration study from construction company inBanda Aceh and Aceh Besar. Generally, construction company in Banda Aceh and Aceh Besar was begin to apply a few of JIT concept in project activity. Although, many of construction company don’t understand what JIT is, benefit and purpose from application this concept in logistic management.